Mineralogical Characterization Studies of Ancient Potteries of Tamilnadu, India by FT-IR Spectroscopic Technique. Issue Volume 7:Issue S1(2010) (2010) - Ravisankar, R.; Kiruba, S.; Eswaran, P.; Senthilkumar, G.; Chandrasekaran, A.
Abstract : We report the spectroscopic investigation of ancient potteries excavated in Tamilnadu. Qualitative analyses were carried out to determine the major and minor constituent minerals present in the samples from the band position or location of the peaks. From the prominent IR absorption peaks, the minerals were identified with the available literature are the quartz, orthoclase, albite, magnetite, hematite, kaolinite, montmorillonite, illite, gypsum and calcite. The interpretation of results is made from the IR characteristics absorption bands. Spectroscopic results indicates that these potteries were refried to a less than 900 ° C.